Theorizing community integration as desistance-promotion - Fox, Kathryn J. (Criminal justice and behavior, 2015)
Recent criminological studies have focused on what promotes desistance from crime, ranging from internal promoters (such as narrative identity shift) to external promoters (such as employment and marriage). An understudied promoter is the role of ordinary community members in integrating released offenders into community life. This article draws on qualitative data collected from a Circles of Support and Accountability (CoSA) program in Vermont, which uses community volunteers to create a circle around selected medium-to-high risk offenders (often sex offenders) who present a risk for reoffense due to their isolation. The nature of the forged relationships is examined, and the article asserts that desistance can be achieved through the actions of community members who communicate a sense of shared moral space, and a genuine sense of belonging. By actively integrating offenders into community life, CoSA model normative lives, create normative and ordinary relationships of mutual obligation and respect, and aid in the de-labeling process by focusing on the other attributes of offenders beyond their criminality. This article concludes by theorizing the role of community integration as an antecedent to desistance, rather than an outcome. In so doing, our knowledge of offender reintegration and desistance processes can be more fully understood.